On Generalized Mannheim curves İn The Equform Geometry Of the Galilean 4-Space - Tarla, Sibel; Öztekin, Handan (Fırat University, 2021)
In this paper on curve, we grant a definition of generalized Mannheim curves that we will depict over the Equiform 2 differential geometry of Galilean 4-space. We show some characterizations of generalized Mannheim curves. A new 3 charecterization has been procured among curvatures by employing the Mannheim curve overview.